2003
DOI: 10.1095/biolreprod.102.005389
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antimicrobial Defensins in the Male Reproductive Tract of Rats, Mice, and Humans1

Abstract: Defensins are antimicrobial peptides that play a major role in innate immunity. Using reverse transcriptase-polymerase chain reaction, immunochemistry, or both, we performed a search of all presently known defensins in rat testis, epididymis, and isolated testicular cells; in mouse testis and epididymis; and in human testis and ejaculates. In the rat, all alpha- and beta-defensins except RNP-4 were expressed within the testis, whereas alpha-defensins RNP1-2, RNP-4, and beta-defensins RBD-1 and RBD-2 were prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 45 publications
4
123
0
4
Order By: Relevance
“…One report observed HD-5 peptide at various sites in the human female genital tract and found high ng͞ml levels of HD-5 in vaginal wash material (48). Other studies have reported HD-5 expression in the testes and male urethra, as well as in breast milk and keratinocytes of the oral and airway mucosa (49)(50)(51)(52)(53). In some of these studies, HD-5 expression appeared to correlate with local inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…One report observed HD-5 peptide at various sites in the human female genital tract and found high ng͞ml levels of HD-5 in vaginal wash material (48). Other studies have reported HD-5 expression in the testes and male urethra, as well as in breast milk and keratinocytes of the oral and airway mucosa (49)(50)(51)(52)(53). In some of these studies, HD-5 expression appeared to correlate with local inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…[60][61][62]95,96 These investigators also showed that several defensins are expressed in murine and human testes, and may contribute to the innate antimicrobial defense. 97 Recent studies have revealed that various PRRs are abundantly expressed in testicular cells and initiate testicular innate immune responses. The PRR-initiated innate responses would be important for testicular cells to overcome immune privilege and elicit an appropriate local response against pathogen invasion.…”
Section: Testicular Innate Immunitymentioning
confidence: 99%
“…This response involves the secretion of cytokines and antibacterial substances, such as b-defensins (Froy 2005, Kogut et al 2006. TLRs and b-defensins have been identified as the key components of innate immune recognition in the reproductive tract of male vertebrate species, providing the first line of defense against potential pathogens (Li et al 2001, Com et al 2003, Palladino et al 2003, Avellar et al 2004, Nishimura & Naito 2005, Rodrigues et al 2008, Anastasiadou et al 2011. Cytokines are essential for the activation, differentiation, and control of the immune system and also play a key role in initiating innate and adaptive immune responses (Hiscott & Ware 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the involvement of TLRs, b-defensins, and cytokines in the interactions between the immune and reproductive systems, as well as the involvement of these molecules in the physiology of reproduction and their existence in the male reproductive tract in various vertebrate species (Jia et al 1999, Com et al 2003, Riccioli et al 2006, Anastasiadou et al 2011. Furthermore, recent studies have reported that mammalian SCs express several TLRs and cytokines that can produce proinflammatory and anti-inflammatory effects (Hedger & Meinhardt 2003, Bhushan et al 2009, Guazzone et al 2009).…”
Section: Introductionmentioning
confidence: 99%